The Effects of ESG activity recognition of corporate employees on job performance: The case of South Korea - Minsuck Jin; Bo-Young Kim (Journal of Risk and Financial Management, 2022)
Corporate environment, society, and governance (ESG) management activities have recently been consolidated in the business ecosystem, and many firms are considering their employees' recognition and job changes according to organizational ESG strategy. This study aims to verify the effects of ESG activity recognition of corporate employees on job performance by mediating change support behavior, innovative organization culture, and job crafting. This study designs a structural equation model with a hypotheses based on previous studies. A questionnaire survey was carried out targeting large Korean manufacturing companies, and an analysis of 329 response copies was performed. As a result, ESG activity recognition did not directly affect job crafting, but it affected job crafting with the mediation of innovative organizational culture and change support behavior. ESG activity recognition also positively affected job crafting and job performance by mediating change support behavior and an innovative organization culture. Hence, the research shows that an innovative culture and change support behavior within an organization should be considered to improve ESG management performance.
Keywords: 650; change support behavior; ESG activity recognition; innovative organization culture; job crafting; job performance